Penyamakan kulit lapis samak kombinasi dengan bahan penyamak alumunium sebagai bahan penyamak pendahuluan - Bambang Oetojo (Majalah Kulit, Karet, dan Plastik, 1987)
As a tanning material alum salt has similar properties of the basic chromium sulphate. It is, therefore, the purpose of this research is to exchange chromium tannage with alum tannage in pretanning for the vegetable tanned lining leather. In doing such a way the chromium pollution may be eliminated, whereas the alum pretanned lining leather output must be fulfill the physical and chemical requirements as that one of the chrome pretanned. In pretanning the use of  alum tannage varied from 2,5%, 3,0%, 3,5% and 4,0%. Afterwards the subsequent process was vegetable tanning using 30% of mimosa powder. The lining leather output from the research was physical and chemical tested. The practical meaning of this research is that for pretanning the vegetable tanned lining leather it is possible to use 2,5% alum salt. The values of the physical and chemical test obtained are that the degree of tannage is 94,54, tensile strength is 174,24 kg/cm2, and strength is 22%. Water absorption for 2 hours is 133,01% and for 24 hours is 134,48%. Whereas the flexural endurance is unbreak condition.